Konsep Manajemen Pendidikan Islam Syeh Al-Zarnuji dalam Kitab Ta'lim al-Muta'allim dan KH.M. Hasyim Asy'ari dalam Kitab Ada al-Alim wa al-Muta'allim - Ahmad Saifudin; Toha Ma'sum (Intizam, Jurnal Manajemen Pendidikan Islam, 2022)
The concepts of Al-Zarnuji and K.H.Hasyim Asy‟ari are two thinkers of Islamic education, they not only talk about education but also discuss the management of Islamic education, through their work, namely Ta'lim al-Muta'allim and Adab al-'Alim wa al-Muta'allim covering planning, organizing, actuating, and controlling although it is not as complete as education management which is mostly used in Indonesia. The focus of the study of the concept of Islamic education management perspective al-Zarnuji in the book of Ta'lim al-Mu'ta'allim, the perspective of K.H. Hasyim Asy‟ari in the book of Adab al-'Alim wa al-Muta'allim, on the differences and similarities between the concept of Islamic educational management perspective al-Zarnuji in the book of Ta'lim al-Mu'ta'allim and K.H. Hasyim Asy‟ari in the book of Adab al-'Alim wa al-Muta'allim. The orientation of this paper study is to show that the concepts brought by al Zarnuji in his book are planning, organizing, actuating and controlling, as well as the concept of Islamic education management in the book of Adab al-'Alim wa al-Muta'allim. The striking difference from the form of management of Islamic education expressed by the two books is in the actuating function, where the book of Adab al-'Alim wa al-Muta'allim how to move students and teachers in the teaching and learning process using the Qur‟an and hadith which explains the primacy of the knowledgeable person and the virtues of the knowledge itself while in the book of Ta'lim al-Mu'ta'allim the process of moving it uses the story of a successful scholar in the process of seeking knowledge. And if analyzed with the opinion of Mujamil Qomar, the concepts expressed by al-Zarnuji and Kiai Hashim are suitable, namely planning, organizing, actuating, and controlling